Synthesis, characterization, deoxyribonucleic acid binding and antimicrobial activity of bivalent metal complexes with 2-acetylpyridine isonicotinoylhydrazone - Dhanalakshmi Dornala, Hussain Reddy Katreddi, Anuja Kandukuri, Srinivasulu Kummara, Nagamani Yamaduru Balaramaiah (Journal of Applied Pharmaceutical Science, 2021)
Survey of literature revealed that bivalent metal complexes of nitrogenous heterocyles exhibit diverse structural and pharmacological features. The purpose of this study is to investigate structural and biological applications of metal complexes with 2-acetylpyridine isonicotinoylhydrazone (APINH). Hence Co(II), Ni(II), Cu(II) & Zn(II) compounds with APINH were produced and characterized according to Electrospray Ionization Mass Spectrometry (ESI-MS), Fourier Transform Infrared spectroscopy (FT-IR) and electronic spectral data. The copper complex was also studied using electron spin resonance (ESR) spectroscopy. DNA interactions of complexes were investigated by using UV-spectroscopy. The metal derivatives were examined for antimicrobial action across Bacillus cereus, Staphylococcus aureus, Escherichia coli & Klebsiella pneumonia employing agar-well diffusion process. Conductivity data suggest non-electrolytic behaviour of compounds. FT-IR results indicate uni-negative tridonor nature of ligand. UV-Visible data confirms octahedral structure for the complexes. ESR data suggest covalent nature of Mâ”€L bond. The data indicate that the nickel derivative sticks to DNA more firmly. Copper compound manifests more effectively than other investigated metal derivatives.
Keywords: Analysis, bivalent metal complexes, 2-acetylpyridine isonicotinoyhydrazone, DNA interactions, antimicrobial activity.